Gifted young children : a guide for teachers and parents - Porter, Louise, 1958- (St Leonards, N.S.W. : Allen and Unwin, 1999)
This book is about: A rational for gifted education; The meaning of giftedness; The making of talent; Recognising advanced development in young children; ...
Keywords: Education; Psychology; Gifted children; Early childhood; Gifted children -- Education; Gifted children; Gifted children -- Psychology; Gifted children -- Study and teaching (Early childhood)